Antioxidant Activity and Antibacterial Seaweed Methanol Extract (Sargassum Duplicatum J. Agardh) and Its Potential as a Natural Preservative Alternative to Salted Eggs - Firmansyah, Satria Bagus; Firmansyah, R. Arizal; Hayati, Nur (Faculty of Science and Technology, State Islamic University Walisongo Central Java, 2016)
The research activity of the antioxidant and antibacterial esktrak methanol seaweed Sargussum duplicatum J. Agardh as well as its potential as an alternative natural preservative salted egg has been done. Seaweed extract S. duplicatum Jj. Agardh assayed phytochemistry and the content of total phenolic with variation of temperature. Metabolite secondary in seawed extract obtained through maseration using methanol solvent. The extract are partitioned, R1 and R2. R1 sample is a sample without treatment and sample R2 is a sample with 45 minutes for warming treatment in waterbath temperature to 100 Â°C. Phytochemical content in seawed of S. duplicatum J. Agardh are flavonoid dan steroid. Phytochemical content and phenolic total have positive correlation to antioxidant activity. Antioxidant activity with DPPH method yielded IC50 = 143.03 Î¼g/mL (R1) and 357.95 Î¼g/mL (R2). Antibacterial activity assay carried out trough diffusion method with SSA media (Salmonella-Shigella Agar). Inhibition value toward Salmonella is 1.120 mm and 1.15 mm with control is chloramphenicol. Salmonella sp.is pathogenic bacteria that presents in egg and causes decay on the egg. Discussion about antibacteria activity results of seawed extract of S. duplicatum J. Agardh are suggested to apply toward egg preservation method. Â©2016 JNSMR UIN Walisongo. All rights reserved